FREQUENCY OF WOUND INFECTION IN NON-PERFORATED APPENDICITIS WITH USE OF SINGLE DOSE PREOPERATIVE ANTIBIOTICS - Ali, Kishwar; Latif, Humera; Ahmad, Sajjad (Journal of Ayub Medical College Abbottabad, 2015)
Background: Antibiotics are used both pre and post-operatively in acute appendicitis for preventing wound infection. It has been observed that the routine use of post-operative antibiotics is not necessary in cases of non-perforated appendicitis as only prophylactic antibiotics are sufficient to prevent wound infection. The aim of this study was to see the frequency of wound infection in non-perforated appendicitis with single dose preoperative antibiotics only. Method: This observational study was conducted at the Department of Surgery, Ayub Medical College, Abbottabad from May to November 2014. A total of 121 patients with non-perforated appendicitis were included in the study. Only single dose preoperative antibiotics were used. The patients were followed for wound infection till 8th post-operative day. Results: 121 patients, 56(46.28%) male and 65(53.72%) female were included in the study. The mean age of patients was 27.41±7.12 years with an age range of 18 to 45 years. In the entire series, 7(5.78%) patients developed wound infection. The infection was minor which settled with conservative therapy. Prophylactic antibiotics were found efficacious in 114(94.21%) patients. There was no significant association between wound infection and age and gender. Conclusion: Single dose preoperative antibiotics were found effective in controlling post-operative wound infection without the need of extending the antibiotics to post-operative period in cases of non-perforated appendicitis. Keywords: Non-perforated appendicitis, Wound infection, Prophylactic antibiotics